Evaluation of complications and quality of life of patient after surgical extraction of mandibular impacted third molar teeth - Gunay Gojayeva; Gorkem Tekin; Nesrin Saruhan Kose; Omur Dereci; Yasin Caglar Kosar; Gizem Caliskan (BMC, 2024)
Abstract Background The aim of our study is to evaluate the postoperative complications after the extraction of impacted third molar teeth and to investigate the effects of these complications on the quality of life of patients. Methods Demographic, clinical, and radiological evaluations were conducted, covering factors like age, gender, and tooth position. Clinical measurements, pain and edema assessments, and quality of life evaluations through OHIP-14 scores were performed. Preoperative and postoperative mouth opening, trismus, alveolitis and dehiscence were evaluated. Results A total of 100 patients were included in our study. No significant gender-based differences were found in measurements, pain, or swelling. There was no statistically significant difference between the preoperative and postoperative results of difference A-C, difference B-E, difference A-D, and difference mouth opening. Procedure duration correlated positively with age, alveolar osteitis, trismus, and swelling. Postoperative quality of life, assessed by OHIP-14, demonstrated a negative correlation with age and trismus. It was observed that the gender and the tooth positions of the patients had no effect on the severity of postoperative pain and edema. Conclusions As the age of the patients increases and the duration of the procedure increases, the rate of postoperative complications increases and it is concluded that the quality of life decreases significantly.